Fabric Construction Techniques as Interventions to reducing Girl-child Truancy in Ghana. A case of Trabuom Roman Catholic JHS (International Journal of Scientific Research and Management (IJSRM), 2022)
Ghana as a developing country needs to educate its citizens especially the girl-child for her to become an important personality in the society in which she lives. In view of that, the government since 1992 introduced the FCUBE (Free Compulsory Universal Basic Education) in the country. This policy is to enable every child of school going age to get access to education. In spite of the provision made for the children in the country, only few girls at Trabuom in the Atwima Kwanwoma District of the Ashanti Region of Ghana attend school. Those who attend school do not complete the Junior High School. Although, the District Directorate of Education know the low enrollment level of girls at the Trabuom Roman Catholic School, very little has been researched into. The study sought to introduce some fabric construction techniques such as macramé and crocheting as interventions to reduce girls truancy in school. The qualitative research design was adopted and participatory action research method was employed. In all 45 students between the ages of 12 to 16 years were sampled for the study using purposive and snowball sampling techniques. Primary data was collected using interviews, observations and focus group discussions. The data were analyzed and discussed accordingly. The findings indicate some of the girls do not attend school due to poverty, teenage pregnancy, negative parental attitude towards girl’s education and sexual harassment by some male teachers. The use of some fabric construction techniques such as macramé and crocheting could significantly help increase the enrollment of girls in school.